GC–MS method for metabolic profiling of mouse femoral head articular cartilage reveals distinct effects of tissue culture and development. Issue 9 (September 2019) - Batushansky, A.; Lopes, E.B.P.; Zhu, S.; Humphries, K.M.; Griffin, T.M.
Summary: Objective: The metabolic profile of cartilage is important to define as it relates to both normal and pathophysiological conditions. Our aim was to develop a precise, high-throughput method for gas/chromatography-mass/spectrometry (GC-MS) semi-targeted metabolic profiling of mouse cartilage. Method: Femoral head (hip) cartilage was isolated from 5- and 15-week-old male C57BL/6J mice immediately after death for in vivo analyses. In vitro conditions were evaluated in 5-week-old samples cultured ±10% fetal bovine serum (FBS). We optimized cartilage processing for GC-MS analysis and evaluated group-specific differences by multivariate and parametric statistical analyses. Results: 55 metabolites were identified in pooled cartilage (4 animals per sample), with 29 metabolites shared between in vivo and in vitro conditions. Multivariate analysis of these common metabolites demonstrated that culturing explants was the strongest factor altering cartilage metabolism, followed by age and serum starvation. In vitro culture altered the relative abundance of specific metabolites; whereas, cartilage development between five and 15-weeks of age reduced the levels of 36 out of 43 metabolites >2-fold, especially in TCA cycle and alanine, aspartate, and glutamate pathways. In vitro serum starvation depleted six out of 41 metabolites. Conclusion: This study describes the first GC-MS method for mouse cartilage metabolite identification and quantification. We observed fundamental differences in femoral head cartilage metabolic profiles between in vivo and in vitro conditions, suggesting opportunities to optimize in vitro conditions for studying cartilage metabolism. In addition, the reductions in TCA cycle and amino acid metabolites during cartilage maturation illustrate the plasticity of chondrocyte metabolism during development.